The student admissions program of the Cebu City schools of nursing - Banzon, Celsa R. 1942-
This study investigated the admission guidelines and procedures in seven nursing schools in Cebu City based on interviews of fifty-nine members of the Admission Committees of these schools. Generally, the schools of nursing in Cebu City observe similar procedures which are as follows: submission and evaluation of applicants' credentials, entrance tests, personal interview and physical examination.